2011
DOI: 10.1021/je2009945
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic, Isotherm, and Thermodynamic Studies of the Adsorption of Methyl Orange from Aqueous Solution by Chitosan/Alumina Composite

Abstract: Alumina, a support material, was loaded with chitosan to form a chitosan/alumina composite (CA) and was utilized for removing sulfonated azo-dye methyl orange (MO) from aqueous media in this study. The adsorbents were characterized by Fourier transform infrared (FTIR) spectra to confirm that chitosan was successfully immobilized on alumina, and some functional groups were successfully introduced into the surface of alumina after modification. The effects of pH, the amount of adsorbent, initial concentration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(71 citation statements)
references
References 39 publications
3
61
0
1
Order By: Relevance
“…Figure c also depicts that PEUL has a higher percentage of removal of MB over the EUL and SEUL bio‐adsorbents. Initially, the percentage of removal is higher due to the availability of the adsorbent sites and then it is reduced as a result of the saturation of the sites and the pore diffusion becomes slow …”
Section: Methodsmentioning
confidence: 95%
“…Figure c also depicts that PEUL has a higher percentage of removal of MB over the EUL and SEUL bio‐adsorbents. Initially, the percentage of removal is higher due to the availability of the adsorbent sites and then it is reduced as a result of the saturation of the sites and the pore diffusion becomes slow …”
Section: Methodsmentioning
confidence: 95%
“…Thus, it is extremely important and a necessity to treat dyed industrial wastewater to prevent people or animals from being harmed. Therefore, a number of technologies have been developed to remove MB from effluent, such as degradation, ultrafiltration, electrochemical treatment, ozonation, ion exchange and adsorption …”
Section: Introductionmentioning
confidence: 99%
“…The initial dye concentration offers the necessary driving force to overwhelm the mass transfer resistance of dye molecules between the aqueous phase and the solid phase. Similar trends have been reported for the sorption of MO onto mesoporous carbon material, activated carbon and chitosan/alumina composite …”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the MO sorption onto PUF/AgNPs could be appropriately represented by a pseudo‐second‐order rate process. Analogous results were obtained for the sorption MO onto various sorbents …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation